Cochrane Corner: Hearing aids for mild to moderate hearing loss in adults - Brennan-Jones, Christopher G.; Weeda, Elizabeth; Ferguson, Melanie A. (Taylor & Francis, 2018)
This Cochrane Corner features the review entitled “Hearing aids for mild to moderate hearing loss in adults” published in 2017. In their review, Ferguson et al. identified five randomised controlled trials (RCTs) involving 825 participants, with moderate quality of evidence shown for all domains except adverse effects. Results showed a large beneficial effect of hearing aids on hearing-specific health-related quality of life and listening ability, and a small yet significant beneficial effect on overall health related quality of life. Ferguson et al. concluded that according to the available evidence, hearing aids are effective at improving hearing-specific health-related quality of life, general health related quality of life and listening ability in adults with mild to moderate hearing loss. The evidence supports the widespread provision of hearing aids as the first-line clinical management for those seeking help for hearing difficulties.